Carex camposii subsp. tejedensis (Cyperaceae), a new taxon for Southern Iberian Peninsula based on molecular, morphological and ecological differentiation. - Sánchez-Villegas, Rogelio; Escudero, Marcial; Martín-Bravo, Santiago; Salazar-Mendías, Carlos; Algarra, Jose A.; Luceño, Modesto (Mediterranean Botany, 2023)
Carex camposii Boiss. & Reut., endemic to high mountain ranges in Southern Iberian Peninsula (Sierra Nevada, Sierra de los Filabres and Sierra de Baza), is a morphologically and molecularly well-defined species included in Carex gr. laevigata (subg. Carex, sect. Spirostachyae). We have discovered a population of a morphologically similar species to C. camposii in a different mountain range (Sierra de Tejeda), that displayed some deviant morphological characters and was found in a different habitat from that typical of the species. In order to disentangle the taxonomic status of this population, we have conducted a phylogenetic analysis using five nuclear (ITS, ETS, G3PDH, CATP and GZF) and three plastid (matK, rpS16 and 5’trnK intron) DNA regions. In addition, a morphological analysis including the population from Sierra de Tejeda was carried out. The resulting phylogenetic trees show that the samples of the problematic population are closely related to C. camposii, while the morphological study revealed that a total of nine morphological features did not match those of typical C. camposii. Even though the samples from Sierra de Tejeda are genetically not well differentiated from C. camposii, the morphological and ecological differentiation supports its recognition as a new subspecies, C. camposii subsp. tejedensis. An assessment of its conservation status using IUCN categories and criteria suggests that it could be critically endangered (CR).